Mode-locked Thulium Ytterbium co-Doped Fiber Laser with Graphene Saturable Absorber - Babar, Ibrahim M.; Paul, Mukul C.; Das, Shyamal; Dhar, Anirban; Ahmad, Harith; Harun, Sulaiman Wadi (Photonics Letters of Poland, 2016)
A passively mode-locked Thulium Ytterbium co-doped fiber laser (TYDFL) is demonstrated using a graphene polyvinyl alcohol saturable absorber as the mode-locker. With 980 nm multimode pumping, the laser operates at 1942.95 nm with repetition rate of 11.76 MHz. The pulse width is calculated to be around 52.85 ps. The maximum pulse energy of 1190.5 pJ is achieved at pump power of 1750 mW. Full Text: PDF References J. Sotor et al., "Ultrafast thulium-doped fiber laser mode locked with black phosphorus", Opt. Lett. 40, 3885-3888 (2015) CrossRef J. Wang et al., "152 fs nanotube-mode-locked thulium-doped all-fiber laser", Nature Scientific Reports 6, 28885 (2016) CrossRef I. M. Babar et al., "Double-clad thulium/ytterbium co-doped octagonal-shaped fibre for fibre laser applications", Ukr. J. Phys. Opt. 15, 173-183 (2014) CrossRef Harun et al., "Mode-locked bismuth-based erbium-doped fiber laser with stable and clean femtosecond pulses output", Laser Phys. Lett. 8, 449-452 (2011) CrossRef M. A. Ismail et al., "Nanosecond soliton pulse generation by mode-locked erbium-doped fiber laser using single-walled carbon-nanotube-based saturable absorber", Applied Optics 51, 8621-8624 (2012) CrossRef G. Sobon et al., "Graphene Oxide vs. Reduced Graphene Oxide as saturable absorbers for Er-doped passively mode-locked fiber laser", Opt. Express 20, 19463-19473 (2012) CrossRef G. Sobon et al., "Thulium-doped all-fiber laser mode-locked by CVD-graphene/PMMA saturable absorber", Opt. Express 21, 12797-12802 (2013) CrossRef